Exploratory factor analysis of stem self-efficacy in the context of Malaysian STEM subjects’ high performers - Yaacob, Zaidi; Abdullah, Nabilah; Razali, Fazilah; Syed Aris, Sharipah Ruzaina (Human Resources Management Academic Research Society (HRMARS), 2024)
STEM education has been a topic of interest for many years, among those are the issue of decreasing number of students showing interest in continuing the academic pathway in STEM. It is also a global issue where among who refuse to take up STEM pathways are those who are high performer students. Among the factors that lead to this situation is low STEM self-efficacy. This study aims to validate the measurement model for the STEM self-efficacy construct in the context of Malaysian STEM subjects’ high performers. Generally, the Exploratory Factor Analysis (EFA) is needed to uncover the suitable items to be used in research instruments. This study adopted a purposive research sampling with data collected from the Law and TESL fundamentals students enrolled in a public university in Malaysia. Items with a 10-interval scale were used. Using the Principal Component extraction method with Varimax Rotation, the researchers performed the EFA procedure on construct elements using SPSS software. Bartlett’s Test of Sphericity and the Kaiser-Meyer-Olkin (KMO) sampling adequacy were also performed. Cronbach’s alpha was used to test the reliability of the retained items. All the 15 items for STEM self-efficacy are retained. Based on the factor analysis, this study finalized the instrument of 15 STEM self-efficacy items; yielding 3 dimensions, i.e., science self-efficacy (7 items), engineering self-efficacy (5 items), and mathematics self-efficacy (3 items). This study explained in detail the procedures for carrying out the STEM self-efficacy construct. The researcher hopes that this study adds new insight into STEM self-efficacy, particularly among the high STEM achievers.